Perception regarding learning computer based test during Covid-19 pandemic: Persepsi tentang pembelajaran computer based test selama pandemi Covid-19 - Fuad Husain Akbar; Burhanuddin Daeng Pasiga; Rasmidar Samad; Rini Pratiwi; Ayub Irmadani Anwar; Nursyamsi Djamaluddin; Edy Julianto; Andi Nadwa Tenri Sapada (Makassar Dental Journal PDGI Makassar, 2022)
Background: Education is one of the largest and most complex social sectors that have been negatively affected by Covid-19, which has led to subsequent changes in modes of learning and teaching in many universities around the world by introducing e-learning platforms. This online learning method has also been carried out by Hasanuddin University through the SIKOLA. Objective: To determine students’ perceptions regarding the computer-based test (CBT) through the SIKOLA learning plat-form during COVID-19 pandemic. Method: This analytic observational study was design as cross-sectional, using students of Hasanuddin University Faculty of Dentistry as population, which were divided by gender and educational stages. Respon-dents filled out online questionnaires consisting of 6 variables, namely pedagogy, validity, reliability, affective factors, effi-ciency, and safety. Data collected were in a form of Likert scale and then analyzed with t-test using SPSS. Result: There was a significant difference in perception between preclinical and clinical students on the pedagogical and efficiency variables (p<0.005). Based on the educational stage, significant differences were only seen in the pedagogical and efficiency aspects. Conclusion: Student perceptions related to CBT exams through SIKOLA learning have good perceptions, seen from the majority of respondents who agree on the pedagogical aspects, validity, reliability, affective factors, efficiency and safety.